Transcatheter arterial embolization of cystic artery bleeding - Kim, Hyo-Cheol; Jeong, Yun Soo; Han, Kichang; Kim, Gyoung Min (Frontiers in Surgery, 2023)
Purpose: The purpose of this study is to report on the safety and clinical outcomes of transcatheter arterial embolization (TAE) by way of the cystic artery for treatment of patients with bleeding from the cystic artery. Materials and Methods: This retrospective study included 20 patients who underwent TAE by way of the cystic artery between January 2010 and May 2022. A retrospective review of radiologic images and clinical data focusing on causes of bleeding, procedure related complications, and clinical outcomes was conducted. Technical success was defined as disappearance of extravasation of contrast media or pseudoaneurysm demonstrated on completion angiography. Clinical success was defined as discharge from the hospital with no bleeding related problem. Results: The most common cause of bleeding was hemorrhagic cholecystitis, followed by iatrogenic, duodenal ulcer, tumor, and trauma. The technical and clinical success rates were 100% and 70%, respectively. Three patients developed ischemic cholecystitis as a complication. Clinical failure occurred in six patients, who all died within 45 days after embolization. Conclusion: Despite a high rate of technical success with use of TAE by way of the cystic artery for treatment of patients with bleeding from the cystic artery, clinical failure may not be an uncommon occurrence.